The dependence of spectral parameters in the cross-sectional equation of coherent and incoherent radiation on energy using a mathematical method - Karyakos, Raed Sabeeh; Yacoob, Ilham M.; Slewa, Muna Y.; Banoosh, Amal M. (Iraqi Journal of Science, 2021)
The dependence of the cross-section of the coherent and incoherent radiation peaks in the X-ray absorption experiment of different energies (20-800 Kev) was investigated. Cross-sectional dependence on the atomic number Z was included from the published data for (8) elements, ranging from carbon to silver (C-Ag). The proportional constant K was obtained between (σc/σi), with the atomic number Z from (6-47). The results show that the value of K exponentially changes with energy.